Genetic polymorphism analysis of cytochrome P4502E1 (CYP2E1) in a Chinese Tibetan population. Issue 47 (November 2017) - Wang, Li; Ren, Guoxia; Li, Jingjie; Zhu, Linhao; Niu, Fanglin; Yan, Mengdan; Li, Jing; Yuan, Dongya; Jin, Tianbo
Abstract : Abstract: Cytochrome P4502E1 (CYP2E1) gene genetic polymorphisms vary markedly in frequency among different ethnic and racial groups. We studied the genotype distributions and allele frequencies of 3 CYP2E1 polymorphisms: CYP2E1 * 1A, CYP2E1 * 7A, and CYP2E1 * 7C by polymerase chain reaction technique in a sample of 100 healthy subjects representing Tibetan population. The frequencies of CYP2E1 * 1A, * 7A, and * 7C alleles were 0.705, 0.125, and 0.170, respectively. Compared with other populations, we found that the allele frequencies of the variants −352A>G (rs2070672) and −333A>T (rs2070673) in this Tibetan population have significant differences compared with European-American, African-American, Japanese, Korean, and other different geographic areas in Chinese Han population. Furthermore, the results of protein prediction revealed that the variant 6397G>A (rs61710826) could influence the protein structure and function. These findings in this study would be valuable for pharmacogenetics for drug therapy and drug discovery. However, further studies in larger samples are warranted to confirm our results.